Cytokines in Male Fertility and Reproductive Pathologies: Immunoregulation and Beyond - Loveland, Kate L.; Klein, Britta; Pueschl, Dana; Indumathy, Sivanjah; Bergmann, Martin; Loveland, Bruce E.; Hedger, Mark P.; Schuppe, Hans-Christian (Frontiers in Endocrinology, 2017)
Germline development in vivo is dependent on the environment formed by somatic cells and the differentiation cues they provide, hence the impact of local factors is highly relevant to the production of sperm. Knowledge of how somatic and germline cells interact is central to achieving biomedical goals relating to restoring, preserving or restricting fertility in humans. This review discusses the growing understanding of how cytokines contribute testicular function and maintenance of male reproductive health, and to the pathologies associated with their abnormal activity in this organ. Here we consider both cytokines that signal through JAKs and are regulated by SOCS, and those utilizing other pathways, such as the MAP kinases and SMADs. The importance of cytokines in the establishment and maintenance of the testis as an immune-priviledged site are described. Current research relating to the involvement of immune cells in testis development and disease are highlighted. This includes new data relating to testicular cancer which reinforce the understanding that tumourigenic cells shape their microenvironment through cytokine actions. Clinical implications in pathologies relating to local inflammation and to immunotherapies are discussed.